Observations on the Cell Biology of Tissue Factor in Endothelial Cells - Andoh, Kiyoshi; Pettersen, Kjell Sverre; Filion -Myklebust, Christiane; Prydz, Hans (Thrombosis and Haemostasis, 1990)
Human umbilical vein endothelial cells (HUVEC) are inducible for tissue factor (TF) activity in culture. Based on experiments using ECGF (4–20 µg/ml) with heparin (90 µg/ml), we obtained the followingresults: 1) In confluent HUVEC cultures, ECGF had essentially no influence on the levels of inducible TF. 2) In growing HUVEC cultures, ECGF reduced the TF response shortly after seeding but full response was regained when cells were kept confluent for 2–3 days. 3) Although secondary cultures responded best to TF induction in the absence of ECGF, the response was essentially equal over at least 8 passages in the prcgcncc of ECGF 1) Of total cellular TF induced in HUVEC, about 25% was available on the surface, and less than 4% was released with theshed plasma membrane vesicles. The proportion of total TF a>ctivity available on the surface of mtact cells wasnot influenced by the presence of ECGF 5) T½, for the decay of TF activity induced was 8.3—9.5 h, whereas in HUVEC when protein synthesis was blocked afterIF induction a T½ of about 30 h was found.